Right Wing Political Extremism in the Great Depression. - Bromhead, A; Eichengreen, B; O'Rourke, K (Nuffield College (University of Oxford), 2012)
We examine the impact of the Great Depression on the share of votes for right-wing anti-system parties in elections in the 1920s and 1930s. We confirm the existence of a link between political extremism and economic hard times as captured by growth or contraction of the economy. What mattered was not simply growth at the time of the election but cumulative growth performance. But the effect of the Depression on support for right-wing anti-system parties was not equally powerful under all economic, political and social circumstances. It was greatest in countries with relatively short histories of democracy, with existing extremist parties, and with electoral systems that created low hurdles to parliamentary representation. Above all, it was greatest where depressed economic conditions were allowed to persist.